Patients’ Knowledge, Attitudes, Behaviour and Health Care Experiences on the Prevention, Detection, Management and Control of Hypertension in Colombia: A Qualitative Study - Legido-Quigley, Helena (PLoS One, 2015)
Hypertension is a leading cause of premature death worldwide and the most important modifiable risk factor for cardiovascular disease. Effective screening programs, communication with patients, regular monitoring, and adherence to treatment are essential to successful management but may be challenging in health systems facing resource constraints. This qualitative study explored patients’ knowledge, attitudes, behaviour and health care seeking experiences in relation to detection, treatment and control of hypertension in Colombia. We conducted in-depth interviews and focus group discussions with 26 individuals with hypertension and 4 family members in two regions. Few participants were aware of ways to prevent high blood pressure. Once diagnosed, most reported taking medication but had little information about their condition and had a poor understanding of their treatment regime. The desire for good communication and a trusting relationship with the doctor emerged as key themes in promoting adherence to medication and regular attendance at medical appointments. Barriers to accessing treatment included co-payments for medication; costs of transport to health care facilities; unavailability of drugs; and poor access to specialist care. Some patients overcame these barriers with support from social networks, family members and neighbours. However, those who lacked such support, experienced loneliness and struggled to access health care services. The health insurance scheme was frequently described as administratively confusing and those accessing the state subsidized system believed that the treatment was inferior to that provided under the compulsory contributory system. Measures that should be addressed to improve hypertension management in Colombia include better communication between health care professionals and patients, measures to improve understanding of the importance of adherence to treatment, reduction of co-payments and transport costs, and easier access to care, especially in rural areas.